The workplace constitution from the New Deal to the New Right / Sophia Z. Lee. - Lee, Sophia Z. (Sophia Zoila), 1970- (Studies in legal history., 2014)
Today, most Americans lack constitutional rights on the job. Instead of enjoying free speech or privacy, they can be fired for almost any reason or no reason at all. This book uses history to explain why. It takes readers back to the 1930s and 1940s when advocates across the political spectrum - labor leaders, civil rights advocates and conservatives opposed to government regulation - set out to enshrine constitutional rights in the workplace. The book tells their interlocking stories of fighting for constitutional protections for American workers, recovers their surprising successes, explains their ultimate failure, and helps readers assess this outcome.